The impact of COVID-19 and bushfires on the mental health of Australian adolescents: a cross-sectional study - Joanne R. Beames; Kit Huckvale; Hiroko Fujimoto; Kate Maston; Philip J. Batterham; Alison L. Calear; Andrew Mackinnon; Aliza Werner-Seidler; Helen Christensen (BMC, 2023)
Abstract Background When COVID-19 spread to Australia in January 2020, many communities were already in a state of emergency from the Black Summer bushfires. Studies of adolescent mental health have typically focused on the effects of COVID-19 in isolation. Few studies have examined the impact of COVID-19 and other co-occurring disasters, such as the Black Summer bushfires in Australia, on adolescent mental health. Methods We conducted a cross-sectional survey to examine the impact of COVID-19 and the Black Summer bushfires on the mental health of Australian adolescents. Participants (N = 5866; mean age 13.61 years) answered self-report questionnaires about COVID-19 diagnosis/quarantine (being diagnosed with and/or quarantined because of COVID-19) and personal exposure to bushfire harm (being physically injured, evacuated from home and/or having possessions destroyed). Validated standardised scales were used to assess depression, psychological distress, anxiety, insomnia, and suicidal ideation. Trauma related to COVID-19 and the bushfires was also assessed. The survey was completed in two large school-based cohorts between October 2020 and November 2021. Results Exposure to COVID-19 diagnosis/quarantine was associated with increased probability of elevated trauma. Exposure to personal harm by the bushfires was associated with increased probability of elevated insomnia, suicidal ideation, and trauma. There were no interactive effects between disasters on adolescent mental health. Effects between personal risk factors and disasters were generally additive or sub-additive. Conclusions Adolescent mental health responses to community-level disasters are multi-faceted. Complex psychosocial factors associated with mental ill health may be relevant irrespective of disaster. Future research is needed to investigate synergistic effects of disasters on young mental health.